Circulating MicroRNAs as potential biomarkers for cerebral collateral circulation in symptomatic carotid stenosis - Liang, Wenwen; Huang, Bingcang; Shi, Qin; Yang, Xuelian; Zhang, Hanwen; Chen, Wei (Frontiers in Physiology, 2024)
Background: Cerebral collateral circulation (CCC) considerably improves the prognosis of patients with symptomatic carotid stenosis (SCS). This study evaluated the diagnostic value of plasma microRNAs (miRNAs) in determining CCC status in patients with SCS. Methods: This single-center observational study enrolled patients with ≥50% carotid artery stenosis diagnosed using Doppler ultrasound. CCC was assessed using cerebrovascular digital subtraction angiography (DSA). Quantitative reverse transcription–polymerase chain reaction was used to determine the expression levels of plasma miRNAs. A multivariate logistic regression model and receiver operating characteristic (ROC) curve were used to analyze the diagnostic value of plasma miRNA expression in determining CCC status. Results: A total of 43 patients were enrolled (28 with CCC and 15 without CCC). The plasma expression levels of miR-126-3p, miR-132-3p, and miR-210-3p were significantly higher and those of miR-16-3p and miR-92-3p were significantly lower in patients with CCC. After adjusting for age, gender, drinking history, comorbidities and degree of SCS, miR-92a-3p, miR-126-3p, miR-132-3p, and miR-210-3p were found to be significantly associated with CCC establishment (p < 0.05). ROC curve analysis indicated a high diagnostic value of these miRNAs in determining CCC status (area under the curve [AUC]: 0.918–0.965), with miR-126-3p exhibiting the highest predictive performance (AUC: 0.965). Subgroup analysis revealed that patients with CCC who had 50%–70% stenosis showed significantly higher expression level of miR-126-3p, whereas those with CCC who had 70%–99% stenosis showed significantly higher expression levels of miR-126-3p, miR-132-3p, and miR-210-3p as well as significantly lower expression levels of miR-15a-3p, miR-16-3p, and miR-92a-3p. Conclusions: The results indicate that these six plasma miRNAs have promising diagnostic value in determining CCC status in varying degrees of SCS. These miRNAs can serve as biomarkers for CCC status following SCS, with miR-126-3p showing the strongest positive correlation.